Implementation of the Principle of Equality Before The Law in Corruption Court Decisions - Sakti, Agam; Aprianingsih, Nina; Nufus, Saifun (JURNAL RUANG HUKUM, 2022)
Equality before the law is a basic principle in positive law in Indonesia which is called the Principle of Equality Before The Law, this aims to protect the human rights of citizens and to fight discrimination and the arbitrariness of rulers, but in practice, there are still many constitutions that have not been carrying out these basic principles, especially in acts of corruption as occurred in the corruption case in the procurement of 1,800 computer units for the 2018 computer-based National Examination worth Rp. This case clearly shows that the law in Indonesia tends to side with the authorities so a stigma arises in society that the law in Indonesia is blunt up and down. Of course, this phenomenon has reduced public trust in the government, especially in law enforcement